2019
DOI: 10.13083/reveng.v27i5.889
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Nível De Ruído Emitido Por Um Trator Agrícola Acoplado a Uma Colhedora De Milho

Abstract: Objetivou-se com o presente trabalho avaliar e comparar o nível de ruído emitido por um trator acoplado a uma colhedora de milho durante a operação agrícola em diferentes rotações do motor, visando identificar zonas de salubridade para os trabalhadores. O experimento foi conduzido no município de Corumbá de Goiás-GO, durante o período de colheita de milho, em julho de 2015. Os dados de nível de ruído foram coletados utilizando-se um medidor de nível de pressão sonora digital, sendo coletados em área livre de o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
1
5
0
1
Order By: Relevance
“…Abnt, 2017) andNR-15 (MTP, 2022), which is 85 dB(A) for 8 h of daily exposure.Souza et al (2005) andSouza et al (2006) found noise levels between 73 and 87 dB(A) in the coffee harvesting operation, using engines similar to the one used in this work Damasceno et al (2019). also found a reduction in the noise level when moving away from the emitting source of a tractor pulling a corn harvester.Although the noise values obtained in this work are below 85 dB(A), according to the Environmental Risk Prevention Program, if the values found are below the tolerance threshold and above the action level (80 dBA),…”
supporting
confidence: 60%
“…Abnt, 2017) andNR-15 (MTP, 2022), which is 85 dB(A) for 8 h of daily exposure.Souza et al (2005) andSouza et al (2006) found noise levels between 73 and 87 dB(A) in the coffee harvesting operation, using engines similar to the one used in this work Damasceno et al (2019). also found a reduction in the noise level when moving away from the emitting source of a tractor pulling a corn harvester.Although the noise values obtained in this work are below 85 dB(A), according to the Environmental Risk Prevention Program, if the values found are below the tolerance threshold and above the action level (80 dBA),…”
supporting
confidence: 60%
“…The use of personal protective equipment is essential to preserve the physical integrity of machine operators and should be used in short working distances of these (Damasceno et al, 2019;Poje et al, 2016;Oliveira et al, 2020) , even if the levels inside the cabin have reached levels below the critical values recommended by the NR15 standard, in a preventive way it may be interesting to use personal protective equipment (Baesso et al, 2017) in all operations with agricultural tractors.…”
Section: Resultsmentioning
confidence: 99%
“…Older tractors, due to the materials used in their components and ergonomic deprivation, emit higher noise levels and, for the most part, do not have a cab for acoustic insulation (MION et al, 2009;BAESSO et al, 2017;CHAIBEN NETO et al, 2020;GOMES et al, 2021). The absence of a cabin causes an increase of approximately 15 dB(A) in the noise level, since noise occurs around the cabin above the recommended limit of 85 dB(A), indicating extremely uncomfortable working conditions (SANTOS FILHO et al, 2004;RINALDI et al, 2008;DAMASCENO et al, 2019;FARIAS & SCHLOSSER, 2020).…”
Section: Noise Levels In Agricultural Tractorsmentioning
confidence: 99%
“…However, the activation of implements driven or driven by power take-off (PTO) requires greater engine power, raising the noise levels emitted directly or indirectly (DAMASCENO et al, 2019). Due to the greater effort of the engine, required by the implements, soil preparation operations with plows, harrows, subsoilers and scarifiers, present the highest noise levels, exceeding the daily exposure limits established by NR-15, reaching a value above 96 dB(A), making the use of PPE necessary (ARCOVERDE et al, 2011;WEDGE;SOUZA, 2012;EGELA & HAMED, 2017).…”
Section: Sources Of Noise In Tractorsmentioning
confidence: 99%